Proteomic Analysis of the Quorum-Sensing Regulon in Pantoea stewartii and Identification of Direct Targets of EsaR - Ramachandran, Revathy (American Society for Microbiology, 2013)
The proteobacterium Pantoea stewartii subsp. stewartii causes Stewart's wilt disease in maize when it colonizes the xylem and secretes large amounts of stewartan, an exopolysaccharide. The success of disease pathogenesis lies in the timing of bacterial virulence factor expression through the different stages of infection. Regulation is achieved through a quorum-sensing (QS) system consisting of the acyl-homoserine lactone (AHL) synthase, EsaI, and the transcription regulator EsaR. At low cell densities, EsaR represses transcription of itself and of rcsA, an activator of the stewartan biosynthesis operon; it also activates esaS, which encodes a small RNA (sRNA). Repression or activation ceases at high cell densities when EsaI synthesizes sufficient levels of the AHL ligand N-3-oxo-hexanoyl-l-homoserine lactone to bind and inactivate EsaR. This study aims to identify other genes activated or repressed by EsaR during the QS response. Proteomic analysis identified a QS regulon of more than 30 proteins. Electrophoretic mobility shift assays of promoters of genes encoding differentially expressed proteins distinguished direct targets of EsaR from indirect targets. Additional quantitative reverse transcription-PCR (qRT-PCR) and DNA footprinting analysis established that EsaR directly regulates the promoters of dkgA, glpF, and lrhA. The proteins encoded by dkgA, glpF, and lrhA are a 2,5-diketogluconate reductase, glycerol facilitator, and transcriptional regulator of chemotaxis and motility, respectively, indicating a more global QS response in P. stewartii than previously recognized.